2016
DOI: 10.3748/wjg.v22.i48.10631
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome symptom severity improves equally with probiotic and placebo

Abstract: AIMTo determine the effects of Lactobacillus acidophilus NCFM on irritable bowel syndrome (IBS) symptoms and quality of life (QoL).METHODSIn this randomized triple-blind trial, adult IBS volunteers who were recruited according to Rome III criteria received 109 or 1010 colony-forming units of NCFM or placebo daily for 12 wk. IBS Symptom Severity Score (IBS-SSS), which constituted the primary outcome, and secondary outcomes, including individual IBS symptoms, IBS-related QoL questionnaire, anxiety and depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
142
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(156 citation statements)
references
References 36 publications
4
142
1
9
Order By: Relevance
“…However, as shown in the forest plot of the metaanalysis, most of the included RCTs also did not find significant difference between probiotics and placebo in alleviating anxiety. This is intriguing because some of the other studies (Guyonnet et al, 2007;Lyra et al, 2016;Ostlund-Lagerstrom et al, 2016) with much larger sample sizes produced nonsignificant findings. This is intriguing because some of the other studies (Guyonnet et al, 2007;Lyra et al, 2016;Ostlund-Lagerstrom et al, 2016) with much larger sample sizes produced nonsignificant findings.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…However, as shown in the forest plot of the metaanalysis, most of the included RCTs also did not find significant difference between probiotics and placebo in alleviating anxiety. This is intriguing because some of the other studies (Guyonnet et al, 2007;Lyra et al, 2016;Ostlund-Lagerstrom et al, 2016) with much larger sample sizes produced nonsignificant findings. This is intriguing because some of the other studies (Guyonnet et al, 2007;Lyra et al, 2016;Ostlund-Lagerstrom et al, 2016) with much larger sample sizes produced nonsignificant findings.…”
Section: Discussionmentioning
confidence: 93%
“…With respect to the findings, three studies (Kato-Kataoka et al, 2016;Lorenzo-Zuniga et al, 2014;Pinto-Sanchez et al, 2017) found significant difference between the probiotics and control groups in relieving anxiety, whereas the other nine studies (Begtrup et al, 2013;Feher et al, 2014;Guyonnet et al, 2007;Lyra et al, 2016;Marcos et al, 2004;Ostlund-Lagerstrom et al, 2016;Romijn et al, 2017;Steenbergen et al, 2015;Stevenson et al, 2014) found no significant difference between the two groups. The duration of intervention ranged from 4 weeks to 24 weeks.…”
Section: Basic Information On Included Studiesmentioning
confidence: 93%
See 3 more Smart Citations